(untitled) (ALMUSTOFA: Journal of Islamic Studies and Research, 2025)
The Society 5.0 era demands Arabic language learning that is contextual, communicative, and adaptive to technological developments. This study aims to analyze the educational thought of Mahmud Ismail Shini as presented in Al-‘Arabiyyah li an-Nāsyi’īn and to examine its relevance in addressing the challenges of Arabic language learning in the Society 5.0 era. This research employs a qualitative approach using a descriptive-analytical library research method. The findings indicate that Shini’s approach positions Arabic as a medium of meaningful communication through the gradual organization of learning materials, the integration of the four language skills, and the use of everyday life contexts. The novelty of this study lies in affirming that Mahmud Ismail Shini’s thought can serve as a conceptual foundation for contextual and communicative Arabic language learning that is adaptive to the demands of Society 5.0 through the humanistic integration of educational technology. The implications of this research suggest that the development of Arabic language learning should be directed toward strengthening students’ communicative competence, enhancing active engagement in the learning process, and designing instruction that is socially and pedagogically relevant within the framework of contemporary curricula.